ANALISIS PENGARUH KUALITAS WEBSITE , KEPERCAYAAN, PROMOSI DAN HARGA TERHADAP KEPUASAN PELANGGAN TOKOPEDIA - Furi Indriyani; Lydia Salvina Helling (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
The purpose of this research is to analyze the influence of website quality, trust, promotion and price towards customer’s satisfaction at Tokopedia.com partially and simultaneously. This research used quantitative research and the feature of this research was descriptive. The sample of this research was 100 respondents, with purposive sampling as the sampling technique. The research data was obtained by distributing questionnaires to 100 Respondents. The analysis method used in the research was multiple linear regressions. The result shows that all of independent variables partially and simultaneously have an influence toward customer’s satisfaction to buy at Tokopedia. Hypothesis testing using T-test shows that all of independent variables proven positively and significantly influence to the dependent variable. Hypothesis F-test shows that website quality, trust, promotion and price have significant influence towards customer’s satisfaction at Tokopedia simultaneously.